The cost of dengue vector control programme in Malaysia / P. Raviwharmman Packierisamy - P. Raviwharmman, Packierisamy (2017)
Dengue fever, an arbovirus disease transmitted by Aedes mosquitoes, has spread rapidly, especially in the tropical countries of the Americas and Asia-Pacific regions. It is endemic in Malaysia, with an annual average of 35,403 reported dengue cases from 2001 to 2010. The economic burden of dengue for Malaysia in 2009 was MYR 359.79 million (US$102.2 million) but these estimates are incomplete because the public sector costs of disease control had not been considered. This study estimated the costs of dengue control and prevention in Malaysia and measured the overall economic impact of dengue in the country. It also examined the variations in dengue vector control costs and resources consumption between the District Health Departments (DHDs) and Local Authorities (LAs) to assist informed decision making as to the future roles of these agencies in the delivery of dengue vector control services in Malaysia. Data were collected from representative vector control units of DHDs, State Health Departments (SHDs) and Federal Health Department (FHD) from Ministry of Health Malaysia and the corresponding LAs at the sampled districts. The costs and resources consumption by capital and recurrent items in 2010 were captured. The data was recorded by level in a matrix by line items and functions. Line items consist of human personnel, buildings, vehicles, equipment, pesticides, personal protective equipment (PPE) and outsourcing of fogging services to private pest control companies. A cost analysis of functions includes costs of inspection of premises, larviciding and fogging activities, entomological surveillance and health education activities. For the comparison of costs between service providers, namely the DHDs and LAs, only the vector control activities were considered. Those vector control activities were inspection of premises, fogging and larviciding of potential breeding sites. Malaysia spent MYR 235.05 mil (US$ 73.45 mil) or 0.03% of the country’s GDPfor dengue vector control and prevention. This expenditure represented MYR 5,091 (US$ 1,591) per reported dengue case and MYR 8.58 (US$ 2.68) per capita population. Notably, 92.2% of this spending occurred in the district-level primarily for fogging activities. From this total expenditure, the national DHDs and LAs expenditure were MYR 169.12 mil (US$ 52.85 mil) and MYR 47.63 mil (US$ 14.88 mil) respectively. The comparison of dengue vector control costs between service providers at the sampled districts revealed that the DHDs spent MYR 17.98 mil (US$ 5.62 mil) or MYR 2,172 (US$ 679) per reported dengue case, and LAs spent MYR 8.34 mil (US$ 2.61 mil) or MYR 1,598 (US$ 499) per reported case. The highest expenditure was fogging, being 51.0% of costs for DHDs and 45.8% for the LAs. The DHDs had higher resource costs for human personnel, vehicles, pesticides and equipment. The findings provide some evidence to rationalize delivery of dengue vector control services in Malaysia. The inclusion of control and preventive activities increased substantially the estimated economic burden of dengue to MYR 594.84 mil (US$ 175.71 mil), or 72% above illness costs alone. The quantification of dengue economic burden informs policy makers and stakeholders regarding the implementation of existing and new technologies for controlling dengue.